2021
DOI: 10.1039/d1ra07905k
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclo[6.1.0]nonyne carboxylic acid for the production of stable molecular probes

Abstract: We report a novel strained alkyne, coined BCN acid. This compound participates efficiently in diverse bioorthogonal reactions and allows the facile production of amide probes, which showed superior in vitro stability compared to carbamate analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…In addition, using 1 as amidite allows the possibility to introduce additional handles for multiple and/or orthogonal conjugation due to the presence of the removable DMT protecting group of the linear aminodiol derivative. As carbamates represent the most encountered type of BCN derivatives and are used in prodrug design, 29 we initially chose to attach the scaffold 1 to the BCN carbinol via a carbamate linkage ( Fig. 1 , A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, using 1 as amidite allows the possibility to introduce additional handles for multiple and/or orthogonal conjugation due to the presence of the removable DMT protecting group of the linear aminodiol derivative. As carbamates represent the most encountered type of BCN derivatives and are used in prodrug design, 29 we initially chose to attach the scaffold 1 to the BCN carbinol via a carbamate linkage ( Fig. 1 , A).…”
Section: Resultsmentioning
confidence: 99%
“…Rady et al demonstrated that the presence of a carboxylic acid on the BCN scaffold does not change alkyne reactivity and gives a straightforward approach to derivatize BCN with an amine of choice via amide formation. 29 It was also shown that BCN amide is a better alternative for molecular probe design which require hydrolytic stability in biological media. 29 The synthesis of both linkers A and B started with the preparation of a common intermediate dimethoxytrityl-5N-[(methyl)-benzoyl]-aminopentane-1,3-diol 1 (Fig.…”
Section: Preparation Of Bcn Linker Derivativesmentioning
confidence: 99%
See 3 more Smart Citations